2022
DOI: 10.1111/head.14411
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the COVID‐19 pandemic on headache‐related disability among young adults with migraine

Abstract: Objective The present study aimed to explore the relationship between the COVID‐19 pandemic and headache‐related disability among a sample of young adults with migraine. Background Comorbid psychological symptoms compound migraine‐related disability. Due to COVID‐19 pandemic procedures, many students experienced institutional closures and corresponding increases in depression, stress, and anxiety. The present study sought to examine changes in headache‐related disability before (Spring and Fall of 2019) and du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(97 reference statements)
0
2
0
1
Order By: Relevance
“…In addition, a minimum duration of CHM treatment for 28 days appears to be beneficial for reducing migraine-comorbid anxiety, and preventing the worsening of insomnia, but it has limited effect on depression. However, it is important to note that depression and insomnia might have been affected by the stress caused by the unanticipated COVID-19 pandemic ( Suzuki et al, 2021 ; Buse et al, 2022 ; Thaxter and Smitherman, 2022 ), which was not systematically assessed in this study. Clinical evidence has found that several CHM formulae were effective in controlling anxiety, depression and insomnia, either as independent conditions or as comorbidities of other conditions such as heart failure, chronic obstructive pulmonary disease, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a minimum duration of CHM treatment for 28 days appears to be beneficial for reducing migraine-comorbid anxiety, and preventing the worsening of insomnia, but it has limited effect on depression. However, it is important to note that depression and insomnia might have been affected by the stress caused by the unanticipated COVID-19 pandemic ( Suzuki et al, 2021 ; Buse et al, 2022 ; Thaxter and Smitherman, 2022 ), which was not systematically assessed in this study. Clinical evidence has found that several CHM formulae were effective in controlling anxiety, depression and insomnia, either as independent conditions or as comorbidities of other conditions such as heart failure, chronic obstructive pulmonary disease, etc.…”
Section: Discussionmentioning
confidence: 99%
“…This is a secondary analysis of data collected as part of an ongoing internet-based study examining physical health and psychological variables among young adults enrolled at a southern university. 20,28 The current cross-sectional study included data from those who completed the battery between Spring 2017 and Spring 2021 semesters and received modest course credit for their participation.…”
Section: Methodsmentioning
confidence: 99%
“…B. [ 13 , 36 ]), wenngleich sich durchaus auch positive Effekte im Sinne einer reduzierten Kopfschmerzaktivität (z. B. durch geringere Stressbelastung, Abnahme von Reizdichte) beobachten ließen [ 10 ].…”
Section: Introductionunclassified